Pengaruh Strength Training terhadap Peningkatan Massa Otot dan Pencegahan Cedera Olahraga - Suranta Pratama Ginting; Anna R Milala; David Pangaribuan; Yudha Prasetya; Fahri (SPRINTER: Jurnal Ilmu Olahraga, 2026)
Sports activities play a crucial role in improving an individual's quality of life, physical fitness, and overall health. However, individuals must balance adequate physical preparation with increased training intensity and frequency. Neglecting these factors increases the risk of sports injuries. For some individuals who engage in recreational sports activities, as well as professional athletes, injuries such as overuse injuries, ligament sprains, and muscle strains are possible. The purpose of this paper is to analyze the effect of strength training on increasing muscle mass and preventing sports injuries. The research method adopted is a qualitative research method. The results show that strength training is a physical exercise aimed at increasing muscle endurance, muscle mass, and strength through the application of weight to the body, thus preventing sports injuries. The study concluded that muscle mass increases are influenced by strength training. The amount of muscle mass gained is influenced by factors such as the duration of the training and the variety of strength training movements. Furthermore, strength training also plays a role in preventing sports injuries. Strength training plays a significant role in injury prevention because it can strengthen and stabilize joints, ligaments, tendons, and muscles.